PHYSICAL, CHEMICAL AND BIOLOGICAL POTENTIAL HAZARDS IDENTIFICATION OF SLAUGHTERHOUSE AND CHICKEN NUGGETS PRODUCTION PROCESS - Sanito, Raynard c (Jurnal Biologi Udayana; Vol 22 No 1 (2018): JURNAL BIOLOGI UDAYANA, 2018)
ABSTRACT Chicken nuggets, the one of protein rich foods, is produced from the chicken meat through several stages of the process. This research aimed to identify the potential hazards of chicken nuggets process in final products based on physical, chemical and biological hazards perspectives. The hazardous potentials were performed specifically using observations, interviews and investigations in a slaughterhouse unit and production unit. Furthermore, the finding of data was described qualitatively. The results of this study indicated that there were several potential hazards in physical, chemical and biological in a chicken nugget process. The ear problems, exhausted of workers, watered by heat frying oil were the examples of potential hazards in physical. In addition, contamination of heavy metal in product and the expired of food grade oil were an illustration of chemical potential hazards. Then, microorganisms in end products, the source of the pathogen were the examples of biological hazards potential. Finally, it could be concluded that chicken nugget factory possessed the physical, chemical, and biological potential hazards. Key words: observations, interviews, findings, microorganisms.